The policy of regional development, a case-study: Southern Italy - DI NARDI, G. (PSL Quarterly Review, 2014)
After the Second World War, Italian public opinion showed an unexpected interest in the age-old problem of backwardness in the South of Italy. With the reconstruction it became clear that it was not possible to avoid raising the issue of a specific economic policy for the South. Until 1949, emergency measures were taken to deal with the most elementary organizational deficiencies. With the establishment of the “Cassa per il Mezzogiorno” in 1950, a new policy had begun. The case of Italy is especially suitable to show that market forces and economic integration are not sufficient to eliminate economic dualism. JEL: O14, O18, O20, O52